SPECIAL STOP SPACE MODEL (RHK) AT THE INTERSECTION OF BOGOR RED LIGHT NEW IN INCREASING TRAFFIC SAFETY AND EFFICIENCY - Abd. Hasyim, Inayatullah; yulianto, ardan agus (DERECHTSSTAAT, 2015)
ABSTRACT Â RHK is a marker at a red light, the location where the motor must be stopped at the marker and 4 or more wheeled vehicles are not allowed in to the RHK. Bogor is one of the cities that have implemented RHK in traffic but still less socialization. Based on the observation at a red light intersection locations New Bogor, there are riders who do not know the application of the RHK, especially four-wheeled vehicle users, because many drivers do not know what the use of existing red paint his motorcycle image. This research was conducted using a normative juridical approach. This type of research used in the study of this law is the law that is descriptive research. The results of this study it is concluded that (1) There is coordination among stakeholders in the implementation of traffic management in order to improve the safety and efficiency of time in traffic carried by Police Bogor City. The area is usually only seen one or two officers, seen more police officers assisted school children (MCC), Police SA (PSA), municipal police, Transportation Department, the military and others. The impact location is usually chaotic start neat. (2) Barriers to improving the safety and efficient traffic include a) the mental attitude of the majority community of users who are less orderly way, selfish and do not meet the traffic regulations; b) The increasing number of motor vehicles; c) The proliferation of street vendors in the streets and bodies at the crossroads; d) Non-availability of adequate parking; e) Not his planned General Plan Spatial (RUTRW). The effort is to do with preventive measures (prevention) and repressive efforts (repression). Â Keywords: Model, Space Special Stop (RHK) Safety, efficiency Traffic